Genetic diversity of Costa Rican populations of the rice planthopper Tagosodes orizicolus (Homoptera: Delphacidae) - Hernández, Myriam (2004)
Tagosodes orizicolus (Homoptera: Delphacidae) is one of the main constraints of the rice production in the Neotropics. This planthopper produces severe damages as a phloem feeder, causes mechanical injury during oviposition and vectors the rice hoja blanca virus (RHBV). The main objective of this study was to determine the genetic diversity of T. orizicolus populations from three rice growing regions of Costa Rica, using RAPDs. Individuals from Guanacaste, Parrita, San Carlos and Cali-Colombia, as outgroup, were analyzed using the random primers. Phenetic relationships revealed that the Costa Rican populations were clearly separated from Cali-Colombia, sharing less than 25% similarity. Costa Rican populations were divided into two main branches separated at 30% similarity. The first branch included Guanacaste and San Carlos and the second displayed Parrita. In relation to similarity indexes within groups, the Guanacaste cluster showed the highest (over 50%) and Cali-Colombia was the most diverse (28%). The correspondence analysis confirmed the clusters of the phenogram and showed close interactions between the Parrita and San Carlos populations. The genetic separation observed could be the result of the geographic isolation among populations, but it could also be explained by the infection with the rickettsia Wolbachia pipientis. This bacterium causes cytoplasmic incompatibility in its host, which results in non-viable progeny when infected males mate with non-infected females, or when insects hosting different strains of Wolbachia mate. Then, a search for Wolbachia in previously described populations of T. orizicolus was initiated. The presence of the bacteria was analyzed by PCR with 16S rDNA-specific primers for Wolbachia. The PCR analyses revealed infections of 86% in the population of San Carlos, 96% in Guanacaste, 37% in Parrita and 100% in Cali-Colombia. Crosses between individuals of T. orizicolus from Parrita and Guanacaste were performed for testing cytoplasmic incompatibility. When infected males were crossed with non-infected females within the same population, a significant reduction in progeny number was obtained as well as when crosses between infected individuals belonging to different populations were performed. These experiments showed cytoplasmic incompatibility not only caused by the presence of Wolbachia within the population, but also by the presence of different strains of the bacteria between populations.